Design and Modification of Janus Polyvinylidene Fluoride/Deacetylated Cellulose Acetate Nanofiber Membrane and its Multifunctionality. Issue 11 (4th March 2023) - Si, Junhui; Zhao, Mingliang; Marcelle, Sansi seukep alix; Wang, Qianting; Cui, Zhixiang; Liu, Xiaolong
Abstract: A novel type of Janus polyvinylidene fluoride/deacetylated cellulose acetate (PVDF/D‐CA) nanofiber membrane with multifunctional application is successfully fabricated by sequential electrospinning. The morphology, chemical composition, surface wettability, oil–water separation performance, and unidirectional liquid transmission capability have been systematically analyzed. It has asymmetric wettability property in air and in liquid systems for its bottom and top sides. It can be used as a water‐removing, or oil‐removing substance for oil–water mixture and emulsion under a harsh environment only under gravity driving force (DF) by simply switching the different sides. It possesses on‐demand water and oil collection ability, and moisture‐wicking performance due to its switchable permeation and unidirectional liquid transmission capability. Its multifunction application can be easy to control by adjusting the thickness of the top and bottom sides through controlling the electrospinning time. Its excellent mechanical property, chemical stability, durability under harsh environment and outstanding anti‐pollution ability endow the membrane with powerful cyclic stability and reusability. Abstract : A novel type of Janus polyvinylidene fluoride/deacetylated cellulose acetate (PVDF/D‐CA) nanofiber membrane with multifunctional application is successfully fabricated by sequential electrospinning. It can be used as a water‐removing, or oil‐removing substance for oil–water mixtures only under gravity driving force (DF) by simply switching the different sides. It possesses on‐demand water and oil collection, moisture‐wicking performance due to unidirectional liquid transmission capability.